Vitasystems theory for aircraft industry development. (17th December 2019) - Ayupov, Abrek I.; Alakoz, Gennady M.; Plyaskota, Sergey I.; Bydanova, Elizaveta N.
The current state of vitasystems theory and the application of a vitasystem approach to the problems of the development of large-scale aerospace complexes, including aircraft industry, are considered.